cosx +cos3x-2cos2x=0
Answers
Answer:
x = nπ ± π / 4 or x = 2nπ
Step-by-step explanation:
Given---> Cosx + Cos3x - 2Cos2x = 0
To find ---> General value of x
Solution---> General value of Cos is
α = 2nπ ± θ
ATQ,
Cosx + Cos3x - 2Cos2x = 0
=> Cos3x + Cosx - 2Cos2x = 0
We know that,
CosC + CosD = 2Cos (C+D/2) Cos (C-D/2)
Applying it we get ,
=> 2 Cos {(3x+x )/2} Cos {(3x - x)/2} - 2Cos2x = 0
=> 2 Cos ( 4x / 2 ) Cos ( 2x / 2 ) - 2 Cos2x = 0
=> 2 Cos2x Cosx - 2 Cos2x = 0
=> 2 Cos2x ( Cosx - 1 ) = 0
If Cos2x = 0
=> Cos2x = Cos π/2
=> Cos2x = Cos ( 2nπ ± π / 2 )
=> 2x = 2nπ ± π /2
=> x = 2nπ / 2 ± π / 4
=> x = nπ ± π / 4
If Cosx - 1 = 0
=> Cosx = 1
=> Cosx = Cos0°
=> Cosx = Cos ( 2nπ ± 0 )
=> x = 2nπ
Answer:
Step-by-step explanation:
cos3x+cosx-2cos2x=0
(cos3x+cosx)-2cos2x=0
Using formula for cosx+cosy
cos3x+cosx = 2cos[(3x+x)/2].cos[(3x-x)/2]
=2cos2x.cosx
Putting this in above eqn
2cos2x.cosx-2cos2x=0
cos2x(cosx-1)=0
Solving for general solutions,
For cos2x=0
x=(2n+1)π/4, n∈Z.
For cosx-1=0
x=2nπ, n∈Z.